Equilibria of vortex type Hamiltonians on closed surfaces - Ahmedou, Mohameden; Bartsch, Thomas; Fiernkranz, Tim (Topological Methods in Nonlinear Analysis, 2023)
We prove the existence of critical points of vortex type Hamiltonians \[ H(p_1,\ldots, p_N) = \sum_{{i,j=1}\atop{i e j}}^N \Gamma_i\Gamma_jG(p_i,p_j)+\Psi(p_1,\dots,p_N) \]on a closed Riemannian surface $(\Sigma,g)$ which is not homeomorphic to the sphereor the projective plane. Here $G$ denotes the Green function of the Laplace-Beltrami operator in $\Sigma$, $\Psi\colon \Sigma^N\to\mathbb{R}$ may be any function of class ${\mathcal C}^1$,and $\Gamma_1,\dots,\Gamma_N\in\mathbb{R}\setminus\{0\}$ are the vorticities. The Kirchhoff-Routh Hamiltonian from fluid dynamics corresponds to $\Psi(p) = -\sum\limits_{i=1}^N \Gamma_i^2h(p_i,p_i)$ where$h\colon \Sigma\times\Sigma\to\mathbb{R}$ is the regular part of the Laplace-Beltrami operator.We obtain critical points $p=(p_1,\dots,p_N)$ for arbitrary $N$ and vorticities$(\Gamma_1,\dots,\Gamma_N)$ in $\mathbb{R}^N\setminus V$ where $V$ is an explicitly given algebraic variety of codimension 1.